Implementasi Knowledge Management Untuk Mendorong Inovasi dan Produktivitas UMKM Menggunakan Big Data Media Sosial - Masbullah, Masbullah (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2023)
Limitations of technology, information management and knowledge management can be overcome with social media. The previous generation of knowledge management was still stagnant and undeveloped, organizations were often trapped and too dependent on knowledge that was lagging behind or stalled. Lack of skills in social media use, lack of awareness of knowledge value management, availability of time to devote both in digital skills and in content creation and duration, create perceived barriers to social media use. Through a concise and relevant knowledge management process, as well as utilizing the use of social media, MSMEs can display and communicate messages, products or services, images, and most importantly, the uniqueness that becomes their selling point. The purpose of this study is to conceptualize the use of social media in an effort to improve the performance of MSMEs in terms of the perspective of knowledge management-based human resource management with a big data model approach for MSMEs. The method used is a review of relevant literature from 2019 to 2023. The results show that the importance of using social media and managing knowledge through big data has a synergistic relationship. revealed that the use of data strategy, a representation of business planning that is guided by knowledge, is a solution for MSMEs in implementing technology through the construction of new knowledge as a tool to encourage innovation and productivity in order to increase business competitiveness and its impact on the performance of MSME actors.